PENGUKURAN BEBAN KERJA PEKERJA RELATIONSHIP MANAGER DIVISI AGRIBISNIS MENGGUNAKAN METODE RATING SCALE MENTAL EFFORT (RSME) DAN MODIFIED COOPER HARPER (MCH) PADA PT IJK - Nabila Zulfa Humahera (2023)
PT IJK, a banking company, faces challenges in its agribusiness division, where duties are no longer separated by commodities. This results in uneven workload and responsibilities between employees. A study was conducted to determine the level of mental workload perceived by workers using the Rating Scale of Mental Effort (RSME) and Modified Cooper Harper Scale methods (MCH). The division's reliance on commodities for client handling leads to a lack of differentiation between departments and clients. The results of the calculation of the mental workload using the RSME method showed that the large workload perceived by 3 employees falls into a very large category, 11 employees fall into a large category and 1 employee falls in a rather large category while the most dominant variable was the workload variable (BK) of 17.74% with an average indicator of 99.13 (overload). The MCH method showed the most dominant mental workload produced at work 3 with a weight of 76.67%. (overload). The proposed improvement plan is to create a system to facilitate the work of a relationship manager, to create new marketing strategies, add a number of employees, and to differentiate departments by sector or commodity.